2014
DOI: 10.3390/ijms15045807
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C Has a Dual Role in Post-Traumatic Brain Injury Recovery

Abstract: Cathepsin B is one of the major lysosomal cysteine proteases involved in neuronal protein catabolism. This cathepsin is released after traumatic injury and increases neuronal death; however, release of cystatin C, a cathepsin inhibitor, appears to be a self-protective brain response. Here we describe the effect of cystatin C intracerebroventricular administration in rats prior to inducing a traumatic brain injury. We observed that cystatin C injection caused a dual response in post-traumatic brain injury recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…By contrast, only a few glia cells in normal brain were seen to contain significant amounts of cathepsin B ( 168 ). A similar intense neuronal cell staining was also seen in rodent brain, especially in the pyramidal cells of the cortex, large neurocytes of the septal region, many hippocampal neurons, and magnocellular nerve cells of the hypothalamus ( 97 , 168 , 172 , 173 ).…”
Section: Mechanisms Of Cathepsin B Regulation In Normal Compared To Tsupporting
confidence: 58%
See 2 more Smart Citations
“…By contrast, only a few glia cells in normal brain were seen to contain significant amounts of cathepsin B ( 168 ). A similar intense neuronal cell staining was also seen in rodent brain, especially in the pyramidal cells of the cortex, large neurocytes of the septal region, many hippocampal neurons, and magnocellular nerve cells of the hypothalamus ( 97 , 168 , 172 , 173 ).…”
Section: Mechanisms Of Cathepsin B Regulation In Normal Compared To Tsupporting
confidence: 58%
“…Our data in a severe CCI mouse model show a 100% and 380% increase in brain cathepsin B activity and protein levels at 2 and 24 h post-trauma, respectively ( 48 ). Trauma elevates cathepsin B protein levels 1 day to 3 days post injury in a moderate closed-skull TBI rat model and this increase varied with injury location ( 97 ). The prolonged elevation of cathepsin B after trauma suggests that it may be possible to therapeutically intervene clinically, as treatment often does not begin until several hours after injury.…”
Section: Traumatic Brain Injury and Tbi-related Injuries Activate Catmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this scale was primarily designed to evaluate cerebral ischemia, cerebral ischemia and trauma share similar pathophysiological mechanisms ( Leker and Shohami, 2002 ). In fact, we have previously used this scale to assess neurological damage after TBI ( Martinez-Vargas et al, 2012 , 2014 ; Estrada-Rojo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…A high level of this biomarker has been observed in the cerebrospinal fluid (CSF) of people who have had a traumatic brain injury, including both children and adults. In addition, many animal experiments have shown that CysC protects the brain from secondary injury by various mechanisms [5,6]. Furthermore, a study of acute cerebral stroke found that CysC was an independent predictor of infarct size and haemorrhage volume [7].…”
Section: Introductionmentioning
confidence: 99%